Price Convergence across Regions in India - Samarjit Das; Kaushik Bhattacharya (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
The paper attempts to examine whether there is price convergence across various regions in India. Our results indicate significant presence of cross-sectional de- pendence in prices in India, rendering some of the standard panel unit root tests inapplicable. Using various panel unit root tests that are robust to cross-sectional dependence, it is found that relative price levels among various regions in India mean-revert. We decompose each series into a set of common factors and idiosyn- cratic components. The decomposition enables us to test stationarity and estimate half-lives of the common factors and the idiosyncratic components separately. Both these components in case of India are found to be stationary. Idiosyncratic price shocks, however, are found to be more persistent as compared to the common factor. The results also indicate that transportation costs proxied by distance can explain a part of the variation in prices between two locations in India.
Keywords: E31; C23; 330; Cross co-integration; Cross-sectional dependence; Panel unit root tests; Common factor; Price convergence